Tradisi Titip sebagai Praktik Utang-Piutang pada Acara Walimatul 'Ursy dalam Perspektif Hukum Islam - Elis Muhlisoh; Mualim Mualim; Yayat Hidayat (AL-MASHALIH (Journal of Islamic Law), 2026)
The titip tradition in walimatul 'ursy (wedding feast) ceremonies has long been practiced by the community of Sembawa Village, Jalaksana District, Kuningan Regency. In this tradition, individuals provide money or goods to those organizing a walimatul 'ursy with the expectation of receiving a similar return when they hold a comparable event in the future. This practice essentially creates an unwritten debt relationship based on mutual trust and local customs. This study aims to analyze the implementation of the titip tradition in walimatul 'ursy ceremonies in Sembawa Village and to examine its conformity with Islamic law. This research employs a qualitative approach and is categorized as field research. Data were collected through semi-structured interviews and documentation, utilizing both primary and secondary data sources. The findings reveal that the titip tradition practiced by the people of Sembawa Village can be classified as a qardh (loan) contract that is permissible under Islamic law, as it fulfills the pillars and conditions of qardh and is supported by the concept of 'urf (custom) that does not contradict Islamic principles. In practice, there are two forms of repayment: repayment with similar objects and repayment with dissimilar objects. Repayment with similar objects is consistent with the provisions of qardh in Islamic law. Meanwhile, repayment with dissimilar objects does not fully comply with one of the requirements of qardh, namely the obligation to return an equivalent object. However, such a practice may still be accepted as long as it is carried out based on mutual agreement and willingness (taradhin) between both parties, without any element of coercion or injustice.